Breadfruit Starch as A Thickener on The Physical and Organoleptic Properties of Tomato Sauce: Peran Pati Sukun Sebagai Pengental Terhadap Sifat Fisik Dan Organoleptik Saus Tomat - Harsanto, Bovi Wira; Triastuti, Indri; Asmoro, Novian Wely; Hartati, Sri (Universitas Slamet Riyadi Surakarta, 2024)
Indonesian people widely consume tomato sauce as a condiment or food seasoning. The natural thickening agent commonly used in tomato sauce is starch, generally based on tapioca or cornstarch. The use of breadfruit starch as a thickener is rarely studied and needs to be researched scientifically. This research aimed to evaluate the role of breadfruit starch as a thickener in tomato sauce. This research began with extracting breadfruit starch through wet milling and continued with making tomato sauce based on breadfruit starch. The concentration of breadfruit starch was varied in 3 levels, namely 0.5%, 1%, and 1.5%. Commercial tomato sauce was also evaluated and used as a comparison. Viscosity, color, and organoleptic analyses were conducted on tomato sauce products. The results showed that tomato sauce based on 1.5% breadfruit starch had a higher viscosity (3220.5 cP) than the addition of 0.5% (572 cP) and 1% (1093.5 cP) starch, but it was still much lower than the viscosity of commercial tomato sauce (6922.5 cP). In terms of color, breadfruit starch-based tomato sauce is not much different from commercial tomato sauce in terms of brightness (L: 32-35), redness (a: 9-11), and yellowness (b: 10-15). After organoleptic analysis, the panelists rated the breadfruit starch-based tomato sauce as mediocre (average score 3), compared to the commercial tomato sauce, which the panelists preferred (score 4). These findings indicate that breadfruit starch has potential as a thickener for tomato sauce because it can resemble the quality of tomato sauce in terms of color. However, the concentration of added breadfruit starch still needs to be increased to increase the thickness of the tomato sauce and its acceptance by consumers.